TRANSFORMASI NOVEL KE FILM BIDADARI-BIDADARI SURGA: KAJIAN EKRANISASI - Putri Nadia Afri; Nurizzati Nurizzati; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
The purpose of this article: (a) to describe story of episode novel Bidadari-bidadari Surga created by Tere Liye, (b) to describe story of episode film Bidadari-bidadari Surga director by Sony Gaokasak, (c) to describe similar and different story of episode novel with film Bidadari-bidadari Surga. The Data of this study were story of episode novel Bidadari-bidadari Surga created by Tere Liye and film Bidadari-bidadari Surga director by Sony Gaokasak. Analyzed technique do with ekranisasi or transformasi theory. The findings of the study showed that the decrease story of episode novel Bidadari-bidadari Surga created by Tere Liye in film Bidadari-bidadari Surga director by Sony Gaokasak become to 85 story of episode. Increase story of episode in film Bidadari-bidadari Surga director by Sony Gaokasak become to 40 story of episode. The happening of change of event variation, figure, and novel story episode background in novel Bidadari-bidadari Surga created by Tere Liye and film Bidadari-bidadari Surga director by Sony Gaokasak become to 35 story of episode.